A Multifaceted Analysis of Place Identity in Urban Planning. Case Study of City of Poznan, Poland - B. Kazmierczak (International Journal of Advanced Science and Technology, 2020)
Downtowns’ public spaces of contemporary large cities are characterized by semantic ambiguity and spatial diversity. What distinguishes them from other urban structures is the fact that the factors determining their attractiveness are the assessments of various users, as well as visitors and those who are related to the place emotionally like local community members. There may occur conflicts in this field, which are caused not only by different needs that individual groups of users want to satisfy within urban public space, but because of the differences in the way they perceive the role of public space in terms of identification and relationship with the space. In the paper there are presented the author’s achievements in the sphere of theoretical research and practical applications of the methodology for downtown public space evaluation in terms of utilitarian, aesthetic and semantic aspects.